Soluble human Suppression of Tumorigenicity 2 is associated with endoscopic activity in patients with moderate-to-severe ulcerative colitis treated with golimumab - Magro, Fernando (2019)
Suppressor of Tumorigenicity 2 (ST2) is an IL33 receptor detected in the mucosa and serum of ulcerative colitis (UC) patients. We evaluated soluble ST2 (sST2) as a surrogate biomarker of disease outcome and therapeutic response, in moderate-to-severe UC patients treated with golimumab.